2012
DOI: 10.1007/s10072-012-0942-z
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia and persistent trigeminal artery

Abstract: We report a case of trigeminal neuralgia caused by persistent trigeminal artery (PTA) associated with asymptomatic left temporal cavernoma. Our patient presented unstable blood hypertension and the pain of typical trigeminal neuralgia over the second and third divisions of the nerve in the right side of the face. The attacks were often precipitated during physical exertion. MRI and Angio-MRI revealed the persistent carotid basilar anastomosis and occasionally left parietal cavernoma. After drug treatment of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…PPTA is usually reported to be detected incidentally and is shown to be rarely associated with pituitary lesions, vascular anomalies, trigeminal neuralgia and aneurysms [3,4]. Four cases of functional macro-adenoma and one case of non-functional adenoma accompanying PPTA have been reported in the literature [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPTA is usually reported to be detected incidentally and is shown to be rarely associated with pituitary lesions, vascular anomalies, trigeminal neuralgia and aneurysms [3,4]. Four cases of functional macro-adenoma and one case of non-functional adenoma accompanying PPTA have been reported in the literature [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…PPTA usually originates from cavernous segment of internal carotid artery (ICA) and contacts with the central part of the basilar artery by coursing inside (medial, intrasellar type) or outside (lateral type) the sella [1]. Although patients are usually asymptomatic, it has been reported that it may accompany third and sixth cranial nerve palsies, aneurysms, vascular anomalies and hemifacial spasm [2][3][4]. The pituitary lesions accompanying PPTA and trigeminal neuralgia (TN) associated with a PPTA are rarely seen [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients may be asymptomatic or present symptoms due to the flow of their posterior circulation or carotid microembolizations from the posterior circulation. In addition to these symptoms, PTA can cause trigeminal neuralgia (3,5).…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of PTAs is generally of uncertain significance, these arteries and their variants have been identified as a rare cause of cranial nerve dysfunction, including incomplete oculomotor nerve palsy, trigeminal neuralgia and hemifacial spasm (3)(4)(5) and sixth nerve palsy (6,7).…”
Section: Sumáriomentioning
confidence: 99%
“…[17] Many authors have shown pain attacks of TN improving with antihypertensive medicines [ Table 1]. [18][19][20][21] However, a systematic and a relatively large-scale study is required to bring up a clear relationship of TN with hypertension. [22]…”
Section: Craniofacial Neuralgiform Pain and Hypertensionmentioning
confidence: 99%